Relationship between the rainfall index for Southern Brazil and the indexes of the Tropical Pacific and the Tropical Atlantic Oceans - Siqueira, Beatriz; Nery, Jonas Teixeira; Carfan, Ana Cláudia (Acta Scientiarum. Technology, 2023)
The proposed study verified the possible influences of sea surface temperature (SST) anomalies in the equatorial Pacific and the tropical Atlantic on the rainfall in the southern region of Brazil. The rainfall stations used have monthly data for the period from 1977 to 2015 and are distributed throughout that region. Monthly TSM anomalies in the Niño 3.4 and Niño 1 + 2 areas, the Southern Oscillation Index and the Monthly Tropical South Atlantic Temperature Index were also used, from the database provided by the Climate Prediction Centre. The results show the association of precipitation in the South region with variations in sea surface temperature in the Tropical Pacific Ocean and, to a lesser extent, with sea surface temperatures in the Tropical South Atlantic Ocean.